2018
DOI: 10.18203/2320-1770.ijrcog20180161
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive sublingual misoprostol for secondary prevention of post-partum hemorrhage during cesarean delivery: double blind placebo randomized controlled trial

Abstract: Background: Cesarean delivery is the most frequently performed major operative procedure worldwide. Objective of present study was to evaluate randomized evidence regarding efficacy and safety of sublingual misoprostol for secondary prevention of post-partum hemorrhage during and after cesarean delivery in women receiving prophylactic oxytocin as primary preventive tools and bleed around 500ml by visual analogue estimation.Methods: A prospective, randomized, double-blind, placebo-controlled trial was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This is in line with Khalafalah [19] as he found that the blood loss was 366.4 ±165 in the carbetocin group and was 434.7 ± 191.7 in the misoprostol group [p=0.01]. In another study done by Sallam and Shady [20] , at Aswan University Hospital comparing misoprostol with placebo in reduced blood loss and prevention of PPH. It was found that high significant reduction in blood loss with misoprostol group than placebo group.…”
Section: Discussionsupporting
confidence: 72%
“…This is in line with Khalafalah [19] as he found that the blood loss was 366.4 ±165 in the carbetocin group and was 434.7 ± 191.7 in the misoprostol group [p=0.01]. In another study done by Sallam and Shady [20] , at Aswan University Hospital comparing misoprostol with placebo in reduced blood loss and prevention of PPH. It was found that high significant reduction in blood loss with misoprostol group than placebo group.…”
Section: Discussionsupporting
confidence: 72%
“…The efficacy of misoprostol alone as well as an adjunct to oxytocin for prevention of PPH is well documented. [9][10][11][12][13][14][15][16][17][18][19][20] In contrast very few studies have reported a contrary view but have used a lower dose. 21 Choosing the optimal dose is imperative to achieve the goal as discussed later.…”
Section: Discussionmentioning
confidence: 99%
“…Misoprostol was compared with a placebo in a different trial conducted by Sallam and Shady [ 28 ] at an Egyptian hospital to determine which drug minimized blood loss and prevented PPH. It was discovered that the misoprostol arm substantially lowered blood loss compared with placebo.…”
Section: Reviewmentioning
confidence: 99%